FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS MANAJEMEN ASET TETAP: PERAN MODERASI SISTEM PENGENDALIAN INTERN : DETERMINANTS OF THE EFFECTIVENESS OF FIXED ASSETS MANAGEMENT: THE MODERATION ROLE OF THE INTERNAL CONTROL SYSTEM - Benny Helmi; Ria Nelly Sari; Alfiati Silfi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to see and determine the direct influence of the factors that affect the effectiveness of fixed asset management: the moderating role of internal control system. The research method used in this research is quantitative. The population in this study is all Regional Apparatus Organizations (OPD) in the Rokan Hilir Regency Government, totaling 48 OPDs, there are three parts of the Apparatus Organization that serve as respondents, namely one user of goods, one administrative officer who uses goods and one person management of user goods so that the number of samples becomes 144 respondents who use Moderated Regression Analysis. The results of this study found the quality of human resources and management information systems affect the effectiveness of fixed asset management. The internal control system can strengthen the influence of the quality of human resources and management information systems on the effectiveness of fixed asset management.